2014
DOI: 10.3233/rnn-130358
|View full text |Cite
|
Sign up to set email alerts
|

Serial treatments of primed low-frequency rTMS in stroke: Characteristics of responders vs. nonresponders

Abstract: Purpose This study analyzed the characteristics of responders vs. nonresponders in people with stroke receiving a novel form of repetitive transcranial magnetic stimulation (rTMS) to improve hand function. Methods Twelve people with stroke received five treatments of 6-Hz primed low-frequency rTMS to the contralesional primary motor area. We compared demographic factors, clinical features, and the ipsilesional/contralesional volume ratio of selected brain regions in those who improved hand performance (N = 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 77 publications
3
44
0
Order By: Relevance
“…In this case, assessing regional WM volume may provide an alternative approach to assess cortical WM integrity. Interestingly, it was recently reported that after stroke, the amount of preserved volume of the ipsilesional posterior limb of the internal capsule is an influential factor when differentiating between rTMS responders and non‐responders (Carey et al ., ). This reinforces the value of segmented WM volume analysis, and further emphasizes the importance of WM preservation for predicting response to rTMS.…”
Section: Discussionmentioning
confidence: 97%
“…In this case, assessing regional WM volume may provide an alternative approach to assess cortical WM integrity. Interestingly, it was recently reported that after stroke, the amount of preserved volume of the ipsilesional posterior limb of the internal capsule is an influential factor when differentiating between rTMS responders and non‐responders (Carey et al ., ). This reinforces the value of segmented WM volume analysis, and further emphasizes the importance of WM preservation for predicting response to rTMS.…”
Section: Discussionmentioning
confidence: 97%
“…DW-MRI has been touted as a promising tool for rehabilitation planning and prognosis after stroke ( 31 ), and may predict neural changes after motor learning. Importantly, preliminary studies have demonstrated that the integrity of CST ( 24 , 34 ) and CC ( 35 ) influences the efficacy of rTMS, suggesting that DW-MRI can provide valuable information when selecting rTMS protocols and predicting the efficacy of an intervention.…”
Section: Neuroimagingmentioning
confidence: 99%
“…Since rTMS is known to modulate cortical excitability in local and remote regions to the areas stimulated, it has been suggested to be a viable therapeutic approach to aid in the recovery of motor function after stroke ( 207 ), yet there is accumulating evidence that the response to rTMS is inconsistent and variable ( 34 , 193 , 194 ). When targeting stimulation over M1, rTMS has been delivered in isolation ( 34 , 208 210 ) and in combination with rehabilitation training ( 193 , 194 , 211 , 212 ) in individuals with stroke.…”
Section: Neuroimagingmentioning
confidence: 99%
“…Numerous neuroimaging studies have identified that motor recovery is related to neural plasticity and cortical reorganization . In recent years, non‐invasive brain stimulation techniques, such as repetitive transcranial magnetic stimulation (rTMS) in particular, have been used to promote functional recovery of stroke patients by modulating cortical excitability and inducing neural plasticity . According to the interhemispheric inhibition model , ‘overactive’ motor areas of the unaffected hemisphere may exhibit abnormally high interhemispheric inhibition to the primary motor cortex (M1) of the affected hemisphere, and thereby weaken motor function and hamper the recovery of the affected extremity.…”
Section: Introductionmentioning
confidence: 99%